Tuesday

March 3, 2015

March 3, 2015

Posted by **Nicholas Lim** on Saturday, January 23, 2010 at 5:32am.

- math -
**drwls**, Saturday, January 23, 2010 at 7:57amFirst write expressions for gf(x) and g^-1(x) in terms of h and k.

Then write equations for gf(-1) and g^(-1)(4)

This will leave you with two equations that involve only h and k.

Solve them simultaneously.

For starters,

gf(x) = h(2-3x) + k = 2h -3hx + k

gf(-1) = 2h + 3h + k = 5h + k

Now compute the inverse function of g and complete the solution.

See if you get

g^-1(x) = [(x-k)/h] + k

**Answer this Question**

**Related Questions**

math-functions - Given g(x)=px+q where p and q are constants.If g^2(x)=16x+15 ...

chemistry - The skeletal structures of the two amino acids, glycine and lysine, ...

calculus - Given the function h : x -> 3x + c and h^-1 : x -> cx/m - 1, ...

Math - The variables x and y are related by the equation y=ax/(x-b),where a and ...

Chemistry - Given the following equilibrium constants are given at 377°C, 1/2 N2...

CORE MATHS - The first two terms in the expansion of (1+ax/2)^10 + (1+bx)^10 in ...

physics - 1.The potiential energy of a particle varies with distance x from a ...

add maths - Functions f and g are defined by f:x→ax-b,where a and b are ...

Math - Let f(x)=2x^2+3px-2q and g(x)=x^2+q,where p and q are constants.It is ...

math (binomial exp) - the Q is : Given that (1+ax)^n = 1 + 30x +375x^2+.... find...